The Human TET2 Gene Contains Three Distinct Promoter Regions With Differing Tissue and Developmental Specificities - Lou, Hong; Li, Hongchuan; Ho, Kevin J.; Cai, Luke L.; Huang, Andy S.; Shank, Tyler R.; Verneris, Michael R.; Nickerson, Michael L.; Dean, Michael; Anderson, Stephen K. (Frontiers in Cell and Developmental Biology, 2019)
Tet methylcytosine dioxygenase 2 (TET2) is a tumor suppressor gene that is inactivated in a wide range of hematological cancers. TET2 enzymatic activity converts 5-methylcytosine (5-mC) into 5-hydroxymethylcytosine (5-hmC), an essential step in DNA demethylation. Human TET2 is highly expressed in pluripotent cells and down-regulated in differentiated cells: however, transcriptional regulation of the human TET2 gene has not been investigated in detail. Here we define three promoters within a 2.5 kb region located 87 kb upstream of the first TET2 coding exon. The three promoters, designated as Pro1, Pro2, and Pro3, generate three alternative first exons, and their presence in TET2 mRNAs varies with cell type and developmental stage. In general, all three TET2 transcripts are more highly expressed in human tissues rich in hematopoietic stem cells, such as spleen and bone marrow, compared to other tissues, such as brain and kidney. Transcripts from Pro2 are expressed by a broad range of tissues and at a significantly higher level than Pro1 or Pro3 transcripts. Pro3 transcripts were highly expressed by embryoid bodies generated from the H9 ES cell line, and the major Pro3 transcript is an alternatively spliced mRNA isoform that produces a truncated TET2 protein lacking the catalytic domain. Our study demonstrates distinct tissue-specific mechanisms of TET2 transcriptional regulation during early pluripotent states and in differentiated cell types.